2021
DOI: 10.3390/pharmaceutics13050631
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Carriers Designed for Encapsulation of Essential Oils with Biological Activity

Abstract: The article reviews the possibilities of encapsulating essential oils EOs, due to their multiple benefits, controlled release, and in order to protect them from environmental conditions. Thus, we present the natural polymers and the synthetic macromolecular chains that are commonly used as networks for embedding EOs, owing to their biodegradability and biocompatibility, interdependent encapsulation methods, and potential applicability of bioactive blend structures. The possibilities of using artificial intelli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 177 publications
(271 reference statements)
0
28
0
Order By: Relevance
“…2007), EO have shown a great potential for treating localized topical bacterial infections (Hollman, 2001) and can even act as a drug delivery vehicle for water insoluble drugs (Chiriac et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2007), EO have shown a great potential for treating localized topical bacterial infections (Hollman, 2001) and can even act as a drug delivery vehicle for water insoluble drugs (Chiriac et al . 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Hopefully, natural products, in particular EO, have showed an excellent antimicrobial activity against many pathogens (Lofa et al 2019;Elcocks et al 2020). Although its clinically applicability might be impaired for systemic infections due to the poorly absorption by the human intestine (Rosato et al 2007), EO have shown a great potential for treating localized topical bacterial infections (Hollman, 2001) and can even act as a drug delivery vehicle for water insoluble drugs (Chiriac et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…The inclusion complexes formed by CDs and EOs improve the EO solubility and physicochemical stability, providing a sustained release of these compounds [ 131 ], also acting as physical barrier to protect the EO in procedures such as freezing, thawing, and/or microwaving during food processing [ 34 ]. In the FI, they are used to improve flavor and sorption of bitter compounds.…”
Section: Nanostructured Delivery Systems (Ndss)mentioning
confidence: 99%
“…To overcome these problems, active agents have been incorporated in polymeric systems allowing their protection and sustained release. Polymer-based systems have shown a longer lasting effect than traditional suspension concentrate formulations, both under experimental and field conditions [ 8 ]. Nanofibrous mats containing citriodiol as biorepellent against Aedes aegypti mosquitoes and its incorporation into a layered fabric were recently studied [ 9 ].…”
Section: Introductionmentioning
confidence: 99%